La “leale collaborazione tra i poteri” ha ultimato la sua parabola. Brevi considerazioni a margine della sentenza della Corte costituzionale n. 242 del 2019 (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Il principio di leale collaborazione tra i poteri in Italia - 3. I significati del principio di leale collaborazione all'interno di un ordinamento - 4. Tipologia di pronuncia della sentenza n. 242 del 2019 - 5. Metodo decisorio della Corte - 6. Considerazioni conclusive.The "loyal collaboration between the powers" has completed its parable. Brief considerations on the sidelines of the Sentence n. 242/2019.ABSTRACT: The Italian Constitutional Court in sentence no. 242 of November 2019 founded its decision to rewrite the contested rule by claiming its power to "manage the constitutional process". The author's aim is to solicit a reflection on the work of the Court which cannot and must not legislate in place of Parliament since only the latter has had the popular mandate in order to implement the laws necessary for the nation.